1988
DOI: 10.1200/jco.1988.6.6.1067
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Tolerability of Low-Dose Cyclophosphamide and Low-Dose Intravenous Interleukin-2 Disseminated Melanoma

Abstract: The title of the article by Mitchell et al published in the March 1988 issue (6:409–424) should have read "Effectiveness and Tolerability of Low-Dose Cyclophosphamide and Low-Dose Intravenous Interleukin-2 in Disseminated Melanoma." The word "in" was erroneously left out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…Despite extensive attempts to assess parameters in the peripheral blood that can predict the outcome of this treatment, only the rebound lymphocytosis after cessation the IL-2 infusion [22] and the lymphokineOffprint requests to: G. G. Hermann activated killer (LAK) cell cytotoxicity induced by IL-2 in vivo [15,17] have been found to relate to the clinical response. The present study was carried out to determine predictors of the clinical effect of IL-2 therapy in metastatic renal cell cancer by measuring a higher number of immunological blood parameters at shorter intervals during IL-2 therapy than investigated in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Despite extensive attempts to assess parameters in the peripheral blood that can predict the outcome of this treatment, only the rebound lymphocytosis after cessation the IL-2 infusion [22] and the lymphokineOffprint requests to: G. G. Hermann activated killer (LAK) cell cytotoxicity induced by IL-2 in vivo [15,17] have been found to relate to the clinical response. The present study was carried out to determine predictors of the clinical effect of IL-2 therapy in metastatic renal cell cancer by measuring a higher number of immunological blood parameters at shorter intervals during IL-2 therapy than investigated in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…(Gemlo et al, 1988;von Rohr et al, 1993). While it is recognised that NK-and LAK-cell activities correlate with tumour responses in animal studies, this is less well established in man (Mitchell et al, 1988). LAK-cell activity, in vivo, has been found to be suboptimal in patients with advanced colorectal cancer receiving continuous infusions of rIL-2 .…”
Section: Pge2 During Ril-2 Infusionmentioning
confidence: 99%
“…However, some authors have demonstrated a direct correlation between a clinical response and increased non-MHC-restricted lytic activity, as observed in IL-2-treated patients with cancer of the head and neck 29 and in IL-2-treated patients after chemotherapy. 30 Conversely, other investigators found no significant correlation at all. 31 One reason for the difference in the results obtained by these groups may be the timing of the blood collections.…”
Section: Discussionmentioning
confidence: 61%